Electrical and Optical Properties of Nickel-Oxide Films for Efficient Perovskite Solar Cells - Hossain M.I.; Hasan A.K.M.; Qarony W.; Shahiduzzaman M.; Islam M.A.; Ishikawa Y.; Uraoka Y.; Amin N.; Knipp D.; Akhtaruzzaman M.; Tsang Y.H. (John Wiley and Sons Inc., 2023)
Conversion efficiency; Finite difference time domain method; Nickel oxide; Optical losses; Oxide films; Perovskite; Perovskite solar cells; Physical vapor deposition; Refractive index; Thin films; Time domain analysis; Complex refractive index; Crystalline properties; Electrical and optical properties; Electrical characteristic; Electron beam-physical vapor deposition; Finite difference time domain simulations; Finite element method simulation; Solar cell structures; Optical films